2002
DOI: 10.1093/treephys/22.5.291
|View full text |Cite
|
Sign up to set email alerts
|

Expression of genes encoding chalcone synthase, flavanone 3-hydroxylase and dihydroflavonol 4-reductase correlates with flavanol accumulation during heartwood formation in Juglans nigra

Abstract: Heartwood formation is generally characterized by the accumulation of phenolic substances that increase the natural color and durability of wood. Although there is evidence that these substances are synthesized in aging sapwood cells, little is known about heartwood formation at the molecular level. We monitored seasonal changes in flavanol concentration across the stems of 23-year-old Juglans nigra L. trees by sampling growth rings extending from the differentiating xylem to the heartwood. We also analyzed ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 46 publications
6
32
0
Order By: Relevance
“…Although it is well known that ray parenchyma cells play an important role in the formation of heartwood, these results indicate that ray parenchyma cells that die earlier are not involved in the formation of heartwood extractives. High-level expression of genes, whose products participate in secondary metabolism at the sapwood-heartwood transition zone, was detected in Juglans nigra and Robinia pseudoacacia (Beritognolo et al 2002;Yang et al 2004). Such genes might not be expressed in the ray parenchyma cells that are in contact with ray tracheids.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well known that ray parenchyma cells play an important role in the formation of heartwood, these results indicate that ray parenchyma cells that die earlier are not involved in the formation of heartwood extractives. High-level expression of genes, whose products participate in secondary metabolism at the sapwood-heartwood transition zone, was detected in Juglans nigra and Robinia pseudoacacia (Beritognolo et al 2002;Yang et al 2004). Such genes might not be expressed in the ray parenchyma cells that are in contact with ray tracheids.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research has shown that in black walnut (Juglans nigra), flavanol biosynthesis was up-regulated in the TZ. Flavonoids are highly soluble polyphenols and in black walnut, the flavanol production was found to be highly correlated with the transcript levels of genes encoding the enzymes chalcone synthase (CHS), flavanone 3-hydroxylase (F3H), and dihydroflavonol 4-reductase (DFR), all of which are implicated in the flavonoid pathway (Beritognolo et al, 2001). At the same time that these genes are being expressed in the TZ, carbohydrate content decreases drastically in this zone.…”
Section: Hw: the Final Transformation Of Xylem Cellsmentioning
confidence: 99%
“…In contrast, there have been only a few large-scale gene analyses for heartwood formation. Studies have been conducted on broad-leaved trees, Robinia pseudoacacia [22,23] and Juglans nigra [24,25], but there have been no reports on conifers. The sugi tree (Cryptomeria japonica D. Don) has sharply defined heartwood, and usually also a readily recognized transition zone (TZ) between sapwood and heartwood [26].…”
Section: Introductionmentioning
confidence: 99%